Emerging Trends in Photobiology: Exploring the Photophysics and Photobiology of the Eye - Ben Okri (International Journal of Photochemistry and Photochemical Research, 2025)
The eye consists of three main segments: the cornea, lens, and retina. The primary function of the anterior ocular tissue, the cornea and lens, is to transmit and focus light onto the retina without distortion. They also filter UV light (under 400 nm), preventing it from reaching the retina. While light reaching the retina is mostly used for vision, it can also have various effects on the eye's constituents, both beneficial and harmful. This article examines how light interacts with the eye, the protective mechanisms involved, and the potential role of light in aging, disease, and other biological processes beyond vision, such as mood, hormonal secretion, and the growth and maintenance of rods and cones.The retina, being sensitive to light, can be affected by prolonged exposure to both visible and UV light, leading to oxidative stress and potential damage. Protective mechanisms, such as antioxidants and carotenoids, play a crucial role in mitigating these risks. Additionally, light influences circadian rhythms and can impact the release of hormones like melatonin, further affecting the body’s internal processes. Understanding the interplay between light exposure, eye health, and systemic biology is vital for the development of interventions to prevent vision loss and preserve overall well-being.
Keywords: and hormonal regulation; carotenoids; circadian rhythms; oxidative stress; protective mechanisms